Development Of Comics Based On Local Wisdom Towards Reading Literacy Student Class IV On Eye Lesson Education Pancasila SDN 104230 Batang District Quiz - Dinda Kasmita (Berpusi Publishing, 2026)
This research is motivated by the limited use of interesting and contextual learning media. in learning Education Pancasila, specifically material diversity culture. This research aim develop media comic based wisdom local Malay For learning Pancasila Education for fourth graders and to determine the feasibility and practicality of the product. The study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, and Implementation. The evaluation stage was not implemented due to time constraints . Data were obtained through interviews, documentation, and documentation. validation sheets from media, language, and material experts, as well as teacher and student response questionnaires. Data analysis was conducted descriptively and quantitatively using percentage score. Results study show percentage eligibility as big as 92.5% from media experts, 88% of linguists, and 92.5% of material experts, all of which are categorized as very suitable. Practicality get percentage 96% based on response Teacher And 91.9% based on response learners, with category very practical. With thus, comic based wisdom local Malay was declared highly suitable and very practical for use as a supporting medium for Pancasila Education learning. This study did not statistically test the improvement in reading literacy skills.